Unemployment: its causes and their remedies - Eason, J. C. M. (Statistical and Social Inquiry Society of Ireland, 1927)
Is unemployment inevitable? If so, are there any remedies which will mitigate its evil effect? These are the questions which are on the lips of those who are compelled to face one of the most vital of the many problems with which civilisation has to grapple.
Read before the Society on Thursday, 11th February, 1926
Keywords: Unemployment rate; Unemployment relief; 314.15